2007
DOI: 10.1007/s10495-007-0154-9
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and autophagy: regulatory connections between two supposedly different processes

Abstract: Apoptosis and autophagy are genetically-regulated, evolutionarily-conserved processes that regulate cell fate. Both apoptosis and autophagy are important in development and normal physiology and in a wide range of diseases. Recent studies show that despite the marked differences between these two processes, their regulation is intimately connected and the same regulators can sometimes control both apoptosis and autophagy. In this review, I discuss some of these findings, which provide possible molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
388
4
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(429 citation statements)
references
References 93 publications
18
388
4
3
Order By: Relevance
“…The autophagy response involving FADD is much more pronounced when apoptosis is blocked, i.e., by caspase inhibition. This suggests that autophagy and apoptosis are induced simultaneously by the FADD death domain, at least in normal epithelial cells (Thorburn 2008), but since apoptotic cell death progresses faster, this is a dominantly observed form of cell death. The full onset of autophagy (or necrosis) emerges only when caspase inhibitors are applied.…”
Section: Other Interconnections Between Apoptotic Necrotic and Autopmentioning
confidence: 99%
“…The autophagy response involving FADD is much more pronounced when apoptosis is blocked, i.e., by caspase inhibition. This suggests that autophagy and apoptosis are induced simultaneously by the FADD death domain, at least in normal epithelial cells (Thorburn 2008), but since apoptotic cell death progresses faster, this is a dominantly observed form of cell death. The full onset of autophagy (or necrosis) emerges only when caspase inhibitors are applied.…”
Section: Other Interconnections Between Apoptotic Necrotic and Autopmentioning
confidence: 99%
“…One study has shown that when placed in culture, amnion epithelial cells are capable of endocytosis and autophagy (selfeating) to adapt to the abrupt changes in the environment (19). For many cell types, the process of autophagy has been well-studied in relation to cellular adaptation to stress and as means to delay apoptosis in low nutrient conditions (20,21 Articles Papanna et alturn to autophagy or apoptosis in response to changes in AF concentration occurring in vivo such as in instances of polyhydramnios (e.g., the recipient sac of pregnancies with TTTS) or postamnioinfusion during FLS procedures. The objectives of this study were: (i) to explore systematically the array of histological changes of the fetal membranes occurring post-FLS for TTTS both at the trocar insertion site and at distance; (ii) to explore whether over-dilution of AF on the recipient side which is a common phenomenon in TTTS pregnancies could be mechanistically linked to histologic changes in the amniochorion and to the high incidence of PPROM post-FLS.…”
mentioning
confidence: 99%
“…One study has shown that when placed in culture, amnion epithelial cells are capable of endocytosis and autophagy (selfeating) to adapt to the abrupt changes in the environment (19). For many cell types, the process of autophagy has been well-studied in relation to cellular adaptation to stress and as means to delay apoptosis in low nutrient conditions (20,21 Articles Papanna et al…”
mentioning
confidence: 99%
“…The discovery of autophagy-related proteins in yeast has revealed the existence of an evolutionarily conserved mechanism for the formation of autophagosomes that sequester cytoplasmic material before they fuse with the endo/lysosomal compartment [3,4]. Light chain 3-II (LC3-II) is specifically located on double membrane-bound autophagosomes that envelop disused proteins or organelles.…”
mentioning
confidence: 99%